Kajian Sosiologi Hukum terhadap Potret, Eksistensi dan Peran Alumni Program Studi Magister Ekonomi Syariah Pascasarjana IAIN Kudus Tahun 2016-2021 - Itmam, Muhammad Shohibul; M. Nur, Dany Miftah (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The aim of the research is to find out: (1) a portrait profile of the existence and role of alumni of the Master of Sharia Economics study program at IAIN Kudus and the use of alumni. At the same time knowing the waiting period for sharia economics master's alumni, the relevance of the study program to the needs of the job market and the responses of alumni users. The research is descriptive qualitative using survey methods. The analysis was carried out using percentages and used 3 stages, namely data reduction, data presentation and conclusion drawing. The results of the research, namely a search using the tracer study instrument, provide an illustration that, firstly, a portrait of the existence and role of alumni of the 2016-2021 postgraduate sharia economics master's study program at IAIN Kudus has been well received by the user community in a professional manner with several reasonable adjustments made by parties related to developing the professionalism of alumni performance. Second, the perception of alumni users of the 2016-2021 IAIN Kudus Postgraduate sharia economics master's study program is that they are satisfied with the good and very good records and are proud and helped by the presence of alumni of the sharia economics study program in their workplace with adjustments to certain fields according to the social conditions of society faced by the graduate users. Users suggest increasing alumni competency in the field of foreign languages, especially English, self-development skills or abilities, as well as mastery of technology that needs to be further developed.